Applying mathematical modeling to create job rotation schedules for minimizing occupational noise exposure. - Tharmmaphornphilas W; Green B; Carnahan BJ; Norman BA (AIHA Journal)
This research developed worker schedules by using administrative controls and a computer programming model to reduce the likelihood of worker hearing loss. By rotating the workers through different jobs during the day it was possible to reduce their exposure to hazardous noise levels. Computer simulations were made based on data collected in a real setting. Worker schedules currently used at the site are compared with proposed worker schedules from the computer simulations. For the worker assignment plans found by the computer model, the authors calculate a significant decrease in time-weighted average (TWA) sound level exposure. The maximum daily dose that any worker is exposed to is reduced by 58.8%, and the maximum TWA value for the workers is reduced by 3.8 dB from the current schedule.